Preparação de poliuretana à base de óleo de mamona - Rodrigues, Jucélia Maria Emerenciano (2005)
Polyurethanes are very versatile macromolecular materials that can be used in the form of powders, adhesives and elastomers. As a consequence, they constitute important subject for research as well as outstanding materials used in several manufacturing processes. In addition to the search for new polyurethanes, the kinetics control during its preparation is a very important topic, mainly if the polyurethane is obtained via bulk polymerization. The work in thesis was directed towards this subject, particularly the synthesis of polyurethanes based castor oil and isophorone diisocianate. As a first step castor oil characterized using the following analytical methods: iodine index, saponification index, refraction index, humidity content and infrared absorption spectroscopy (FTIR). As a second step, test specimens of these polyurethanes were obtained via bulk polymerization and were submitted to swelling experiments with different solvents. From these experiments, the Hildebrand parameter was determined for this material. Finally, bulk polymerization was carried out in a differential scanning calorimetry (DSC) equipment, using different heating rates, at two conditions: without catalyst and with dibutyltin dilaurate (DBTDL) as catalyst. The DSC curves were adjusted to a kinetic model, using the isoconversional method, indicating the autocatalytic effect characteristic of this class of polymerization reaction